On solvability of inhomogeneous boundary-value problems in Sobolev—Slobodetskiy spaces - Mikhailets, V.A.; Skorobohach, T.V. (Доповіді НАН України, 2020)
We investigate the most general class of Fredholm one-dimensional boundary-value problems in the Sobolev—Slobodetskiy spaces. Boundary conditions of these problems may contain a derivative of the whole or fractional order. It is established that each of these boundary-value problems corresponds to a certain rectangular numerical characteristic matrix with kernel and cokernel having the same dimension as the kernel and cokernel of the boundary- value problem. The sufficient conditions for the sequence of the characteristic matrices of a specified boundary-value problems to converge are found.